The importance of pathogen-free grapevine propagation material in regards to clonal selection and rootstock breeding in Germany - Rühl, E. H.; Manty, F.; Konrad, H.; Bleser, E. (International Journal of Horticultural Science, 2011)
High performing propagation material is essential for a reliable and economical production of quality grapes. Apart from genetic aspects pathogen-freedom is of prime importance in propagation material. In particular virus diseases cause major yield and quality losses and reduced longevity. This is also reflected in the current EU legislation, which focuses on the most common and dangerous viruses: GFLV, ArMV, GLRaV-I and GLRaV-III.Apart from these, locally occurring pathogens, e.g. phytoplasms or agrobacterium, are important as well and should not be present in propagation material. There are several ways to develop pathogen-free clones. Starting with already pathogen-free material is certainly the easiest case, but might not be feasible in local varieties with small acreages and limited vine numbers. In these cases the elimination of pathogens is required, either by heat therapy, tissue culture or somatic embryo genesis.